2015
DOI: 10.2169/internalmedicine.54.3770
|View full text |Cite
|
Sign up to set email alerts
|

HIV-negative Primary Bone Marrow Hodgkin Lymphoma Manifesting with a High Fever Associated with Hemophagocytosis as the Initial Symptom: A Case Report and Review of the Previous Literature

Abstract: A 68-year-old man was referred to our hospital due to a high fever and pancytopenia. Neither tumors nor infectious lesions were detected. Hemophagocytosis was observed on the bone marrow (BM) smear, although without abnormal cells. Prednisolone therapy was ineffective for the patient's high fever. Later on, we obtained the results of a BM biopsy indicating the presence of infiltration of atypical Reed-Sternberg cells, leading to a diagnosis of HIV-negative primary bone marrow Hodgkin lymphoma (PBMHL). However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Unfortunately, more than half of these patients died in the short term, and disease progression was the dominant cause of death. Morita et al21 reported that HIV-negative cases tended to progress rapidly and resulted in worse outcomes, which is consistent with our analysis. Regarding T-cell lymphoma, we first used the gemcitabine, cisplatin, prednisone, and thalidomide regimen in our patients because this regimen was proven to be more efficient than CHOP for the treatment of PTCL in a prospective, randomized, controlled, and open-label clinical trial;22 however, the results were not satisfactory and the results of the CHOP regimen were also not satisfactory.…”
Section: Discussionsupporting
confidence: 93%
“…Unfortunately, more than half of these patients died in the short term, and disease progression was the dominant cause of death. Morita et al21 reported that HIV-negative cases tended to progress rapidly and resulted in worse outcomes, which is consistent with our analysis. Regarding T-cell lymphoma, we first used the gemcitabine, cisplatin, prednisone, and thalidomide regimen in our patients because this regimen was proven to be more efficient than CHOP for the treatment of PTCL in a prospective, randomized, controlled, and open-label clinical trial;22 however, the results were not satisfactory and the results of the CHOP regimen were also not satisfactory.…”
Section: Discussionsupporting
confidence: 93%
“…As no malignant cells were found outside the bone marrow, it is possible that this represented primary bone marrow Hodgkin lymphoma. While this is quite rare and typically associated with HIV infection, for which our patient tested negative, several previous cases have been described of HIV-negative primary bone marrow Hodgkin lymphoma [ 35 , 36 ]. Alternatively, it is possible that the tonsillar biopsy was a false negative and that this represented stage 4 Hodgkin lymphoma.…”
Section: Discussionmentioning
confidence: 70%
“…Therefore, bone marrow biopsy continues to be the gold standard to confirm the involvement of the bone marrow in HL patients with PET/CT employed for follow-up. So far, there are only seven cases of PBMHL reported (Table 1) [10][11][12][13][14][15]. As outlined above, the current first-line combination chemotherapy for HL is ABVD.…”
Section: Discussionmentioning
confidence: 99%